What determines the costs of fiscal consolidations? - Mathias Klein (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Recent studies have proposed several factors that determine how fiscal consolidations affect the economy. This Roundup focuses on several of these determinants. Namely, it discusses how the composition of the consolidation measure, the state of the business cycle, the level of private indebtedness and the amount of fiscal stress during which the measure is implemented influences the consequences of austerity. It seems reasonable to consider these factors more carefully when deciding about the type and timing of fiscal consolidation plans.
Keywords: 330